Cinnamic acid alleviates hypertensive left ventricular hypertrophy by antagonizing the vasopressor activity and the pro-cardiac hypertrophic signaling of angiotensin II - Cui, Yimeng; Yang, Yawei; Tang, Xinmiao; Wang, Peiwei; Cui, Jingang; Chen, Yu; Zhang, Teng (Frontiers in Pharmacology, 2025)
BackgroundHypertension is the most common cause of pathological left ventricular hypertrophy, a condition causally associated with debilitating heart failure and cardiovascular events in hypertensive patients. It is well recognized that the disease burden of hypertension-linked heart failure remains unabated with existing treatments. New therapies controlling hypertensive left ventricular hypertrophy are thus required to decelerate or prevent the development of heart failure. Our previous study has demonstrated that cinnamic acid, a naturally occurring monocarboxylic acid, mitigates transverse aortic constriction-induced pressure overload-mediated cardiac hypertrophy. However, whether cinnamic acid is effective at controlling hypertensive left ventricular hypertrophy remains unknown. Angiotensin II (ang II) plays a pivotal role in driving the pathogenesis of hypertensive left ventricular hypertrophy. The current work thus investigates the therapeutic potential and pharmacological mechanisms of cinnamic acid in the context of ang II-mediated hypertensive left ventricular hypertrophy.MethodsAng II-infused mice and cardiomyocytes were analyzed by histological, immunohistochemical, cellular and molecular biological methods to delineate the impact of cinnamic acid on hypertensive left ventricular hypertrophy.ResultsThe results showed that cinnamic acid lowered blood pressure and attenuated left ventricular hypertrophic and fibrotic alterations in the ang II-infused mice. Cinnamic acid counteracted hypertrophic responses, impairment of the mitochondrial function and overproduction of mitochondrial reactive oxygen species (ROS) in the cardiomyocytes exposed to ang II. At the molecular level, cinnamic acid mitigated ang II-induced activation of signal transducer and activator of transcription 3 (STAT3) and extracellular signal-regulated kinase 1/2 (ERK1/2) in cardiomyocytes. Additionally, cinnamic acid blunted STAT3 and ERK1/2 activation as well as the hypertrophic responses in cardiomyocytes exposed to interleukin 6 (IL-6) as well.ConclusionIn summary, this is the first study demonstrating that cinnamic acid is effective at mitigating hypertensive left ventricular hypertrophy. Cinnamic acid antagonizes the vasopressor activity of ang II at the systemic level and the ligand-dependent pro-hypertrophic signaling of ang II in cardiomyocytes. Furthermore, our present study presents new evidence supporting that cinnamic acid lessens the activation of STAT3 and ERK1/2, which may in part contribute to its anti-hypertrophic actions in cardiomyocytes.